Pengaruh Suhu Udara Panas Terhadap Bahan Bakar Mesin Bensin - Kurniawan Joko Nugroho; Warsito (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
The process of combustion of fuel in the cylinder is influenced by temperature, mixture density, composition, and turbulence that exists in the mixture. When the temperature of the fuel mixture with the air rises, the easier it is to mix the fuel with the air to catch fire. The research was conducted at the Mesin Otomotif Politeknik Pratama Mulia Surakarta Laboratory in the year 2020. From the average observation experiments using fuel, the following results were obtained: temperature 30-35 ℃, engine speed (RPM), 1500 rpm = 63 ml, 2000 rpm = 80 ml, temperature 45-50 ℃, then the engine speed (RPM) 1500 rpm = 56 ml, 2000 rpm = 70 ml. From the test it can be concluded that the lower the inlet air temperature and the higher the engine speed, the fuel consumption will be different, this is because every increase in the rotation looks fuel consumption also rises.